2018
DOI: 10.1101/428722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the amino-acid transporter LAT1 demonstrates anti-neoplastic activity in medulloblastoma

Abstract: Most cases of medulloblastoma (MB) occur in young children. While the overall survival rate can be relatively high, current treatments combining surgery, chemo-and radiotherapy are very destructive for patient development and quality of life. Moreover, aggressive forms and recurrences of MB cannot be controlled by classical therapies. Therefore, new therapeutic approaches yielding good efficacy and low toxicity for healthy tissues are required to improve patient outcome. Cancer cells sustain their proliferatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…JPH203 was previously reported as potent, LAT1-specific inhibitor. [27][28][29][30][31]46 JX009 had been described in the patent literature 37 to inhibit LAT1-mediated transport with similar efficacy as JPH203, albeit with significantly lower specificity, that is, it is also a potent LAT2 inhibitor. As no other LAT2 inhibitors have been described in the literature, JX009 was considered the best available tool for the assessment of LAT2-related transport of leucine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JPH203 was previously reported as potent, LAT1-specific inhibitor. [27][28][29][30][31]46 JX009 had been described in the patent literature 37 to inhibit LAT1-mediated transport with similar efficacy as JPH203, albeit with significantly lower specificity, that is, it is also a potent LAT2 inhibitor. As no other LAT2 inhibitors have been described in the literature, JX009 was considered the best available tool for the assessment of LAT2-related transport of leucine.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] The substrate-mimicking tyrosine analog JPH203 (also known as was tested in several in vitro and in vivo cancer cell proliferation experiments and described as potent LAT1-specific inhibitor. [27][28][29][30][31] To delineate the contribution of LAT1 from LAT2 in materno-foetal leucine transport, we synthesized the LAT1-specific inhibitor JPH203, the structurally closely related inhibitor (JG336), as well as a third small molecule inhibitor (JX009) with comparable leucine uptake inhibition efficiency but lower LAT1-specificity (structures see Figure 4).…”
mentioning
confidence: 99%
“…Furthermore, other LAT1 substrate amino acids were also reported to be involved in cellular signaling 4 . Recent studies have indicated the link between LAT1 and mTORC1 signaling 22‐24 as well as other signaling pathways 25,26 in cancer cells. Many studies have reported the anticancer effects induced by LAT1 inhibition in various cancer types 22‐24,27‐33 .…”
Section: Introductionmentioning
confidence: 99%
“…In such context, blocking the uptake of amino acid by inhibiting their transporters may represent a viable approach to starve tumors from their widely used metabolites [27]. The effects of amino acid transporter inhibition on reducing tumor viability have been shown in a subset of cancers demonstrating the potential efficacy of such approaches [8,12,28]. For instance, the SLC7A5 (LAT1) inhibitor JPH203 has been tested in clinical trials showing promising effects for the treatment of solid tumors refractory to standard therapy [29].…”
Section: Discussionmentioning
confidence: 99%